Endless siege : education and nationalism in Vidya Bharati schools - Iwanek, Krzysztof (Oxford: Oxford University Press, 2022)
"This book is the only monograph to date on Vidya Bharati: the largest network of private schools in India. These institutions are run by Hindu nationalists of the Rashtriya Swayamsevak Sangh (RSS) and thus are also connected to the party currently ruling India: Bharatiya Janata Party (BJP). The organisation makes for an interesting case: it runs school on an income-basis but its main objective is to spread a nationalist ideology. This work seeks to explain how did Vidya Bharati manage to navigate between these two factors to become such a successful venture. It concludes that Vidya Bharati found itself a wide gap on the Indian education market: its schools are usually much cheaper than elite private ones but also better organised than government institutions. In other cases, they are also found where no other private schools are active and when government schools are moribund. The network not only benefits from functioning in this middle zone, but skilfully hides its affiliation to the RSS and places radical, nationalist accents of its narrative in specific points of the curriculum and school life. The author has made use of original resources (Vidya Bharati school textbooks), as well as visited schools and conducted interviews with school employees"--